MOTIVASI BERWIRAUSAHA, MANAJEMEN WAKTU, MANAJEMEN KEUANGAN, DAN PRESTASI AKADEMIK PADA MAHASISWA WIRAUSAHA - Urfillah, Ulfi; Muflikhati, Istiqlaliyah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2017)
This study aimed to analyze the influence of sample characteristics, family characteristics, business characteristics, entrepreneurial motivation, time management, and financial management toward business growth and academic achievement of college entrepreneurs. The study involved 50 college students (32 male and 18 female) who have been in business (agriculture or non-agricultural) for at least three months. Samples chosen by snowball technique with the first key informant is the head of the entrepreneurial community. Data were collected through interviews and analyzed using independent sample t-test, factor analysis, and multiple linear regression. Research showed that category of entrepreneurial motivation was high. The most motivating factor for college entrepreneurs was a greater business achievement. Category of financial and time management of college entrepreneurs were in the medium. The largest percentage of business growth was between 0,0 to 20,0 percent per month. Female entrepreneurs have better academic achievement than male entrepreneurs. The study found that the business growth is significantly positively influenced by the education and occupation of the father. The academic achievement of college entrepreneurs is negatively influenced by the participation of the Entrepreneurship Student Creativity Program and business growth, but it is positively influenced significantly by college entrance pathways and financial management.